Changes in liver function test levels in HIV patients undergoing highly active antiretroviral therapy (HAART). Longitudinal study in Lima, Peru - Jeel Moya-Salazar; Miriam Barrial-Vega; Ruth Arrieta-Calderón; Hans Contreras-Pulache (Revista de la Facultad de Medicina)
Introduction: Estimating and monitoring changes in liver function tests is necessary to prevent the occurrence of chronic liver disease in HIV patients undergoing highly active antiretroviral therapy (HAART).